IMPROVEMENT OF METHODS OF TREATMENT OF PERSISTENT ATRIAL FIBRILLATION IN PATIENTS WITH ISCHEMIC HEART DISEASE - Rizayeva Malika Jamolovna (International Engineering Journal For Research & Development, 2020)
Atrial fibrillation is the most common arrhythmia encountered in clinical practice and accounts for approximately one third of hospitalizations for cardiac arrhythmias. Cardiac dysfunction may result from myocardial ischemia, rhythm disturbances, valve dysfunction, pericardial damage, increased filling pressure or systemic resistance. Newly developed acute heart failure is most often observed in patients with acute coronary syndrome. The development of decompensation of chronic heart failure is facilitated by low adherence to treatment, fluid overload, infections, alcohol consumption, certain drugs (for example, non-steroidal anti-inflammatory drugs or thiazolidinediones, which cause fluid retention), etc. Acute heart failure is usually accompanied by congestion of blood in the lungs, although in some patients the clinical picture is dominated by signs of decreased cardiac output and tissue hypoperfusion.